THE ROLE OF INNOVATIVE TECHNOLOGIES IN IMPROVING THE QUALITY OF TRANSPORT SERVICES - Akhmatova Mohigul Ergash qizi; Hamroyev Halim Rozikovich (Scholar Express Journals, 2021)
The article suggests methodological tools to identify and assess the development of innovative performance reserves that enhance the quality of road transport services in the region
Keywords: Quality; transport services; innovation; ability